An analysis of economic learning among undergraduates in introductory economics courses in Germany. Issue 4 (1st October 2016) - Happ, Roland; Zlatkin-Troitschanskaia, Olga; Schmidt, Susanne
ABSTRACT: In this article, the authors present the findings of a pretest-posttest measurement of the economic knowledge of students in introductory economics courses in undergraduate study programs in Germany. The responses of 403 students to 14 items selected from the Test of Economic Literacy (Soper and Walstad1987 ) were analyzed to identify four types of economic learning: positive, retained, negative, and zero learning. In addition, a survey was conducted to gather data on the students' personal characteristics to determine their effect on the learning process. Retained learning prevailed for most items, followed by zero learning and positive learning. To determine which factors influence beginning students' acquisition of economic knowledge and lead to positive learning, regression analyses were conducted, and the findings are discussed critically.